Application of Bradford’S Law to Citation Data of History Doctoral Dissertations Accepted By Kurukshetra University: an Analytical Approach: Exploring the Applicability of Bradford's Law to Citation Data of History Doctoral Dissertations (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The applicability of the two vital formulations (verbaland graphical) of Bradford’s Law of scattering were tested. The study has shownthat the verbal formulation of the present study was closer to the graphicalformulation.